Precise 3D/2D calibration between a RGB-D sensor and a C-arm fluoroscope - Wang, Xiang; Habert, Severine; Ma, Meng; Huang, Chun-Hao; Fallavollita, Pascal; Navab, Nassir (International Journal of Computer Assisted Radiology and Surgery, 2016)
Purpose: Calibration and registration are the first steps for augmented reality and mixed reality applications. In the medical field, the calibration between an RGB-D camera and a C-arm fluoroscope is a new topic which introduces challenges. Method: A convenient and efficient calibration phantom is designed by combining the traditional calibration object of X-ray images with a checkerboard plane. After the localization of the 2D marker points in the X-ray images and the corresponding 3D points from the RGB-D images, we calculate the projection matrix from the RGB-D sensor coordinates to the X-ray, instead of estimating the extrinsic and intrinsic parameters simultaneously. Validation: In order to evaluate the effect of every step of our calibration process, we performed five experiments by combining different steps leading to the calibration. We also compared our calibration method to Tsai’s method to evaluate the advancement of our solution. At last, we simulated the process of estimating the rotation movement of the RGB-D camera using MATLAB and demonstrate that calculating the projection matrix can reduce the angle error of the rotation. Results: A RMS reprojection error of 0.5 mm is achieved using our calibration method which is promising for surgical applications. Our calibration method is more accurate when compared to Tsai’s method. Lastly, the simulation result shows that using a projection matrix has a lower error than using intrinsic and extrinsic parameters in the rotation estimation. Conclusions: We designed and evaluated a 3D/2D calibration method for the combination of a RGB-D camera and a C-arm fluoroscope.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 3D/2D calibration; C-arm fluoroscope; Calibration phantom; RGB-D sensor